Measuring serious emotional disturbance in children : workshop summary - Marton, Krisztina (Online access: NCBI NCBI Bookshelf., 2016)
"The workshop summarized in this report was organized as part of a study sponsored by the Substance Abuse and Mental Health Services Administration (SAMHSA) and the Office of the Assistant Secretary for Planning and Evaluation of the U.S. Department of Health and Human Services, with the goal of assisting SAMHSA in its responsibilities of expanding the collection of behavioral health data in several areas. The workshop brought together experts in child mental health, psychiatric epidemiology and survey methods to facilitate discussion of the most suitable measures and mechanisms for producing estimates of serious emotional disturbance in children, which are necessary to enable the distribution of block grants that support state-level mental health services for children. The report discusses existing measures and data on mental disorders and functional impairment, challenges associated with collecting these data in large-scale population-based studies, as well as study design and estimation options"--Publisher description